Diskurse - Institutionen - Individuen Neue Perspektiven in der Übergangsforschung - Pohling, Andrea (Verlag Barbara Budrich, 2022)
Life is structured by a great variety of transitions. How do transitions take place between individual phases of life and status positions, between different roles and self-images? How are transitions discursively negotiated? The contributions in this volume deal with how transitions are produced and shaped through discourse, institutional regulation, and individual learning and coping processes.
"Verlag Barbara Budrich"
Keywords: Life change events.; Life skills.; life trans; Life Change Events; Événements stressants de la vie.; Habiletés de base.; SOCIAL SCIENCE.; Life change events; Life skills; Biographie; biography; development; discourses; Diskurse; Entwicklung; individuals; Individuen; Institutionen; institutions; Lebenslauf; life course; transitions; Übergänge; Electronic books.